North and South [videorecording (DVD)] : complete collection - Heffron, Richard, 1930-; Read, James, 1952-; Swayze, Patrick; Down, Lesley-Anne; Jakes, John, 1932- (Warner Home Video, 2011)
A friendship between two young men becomes difficult when their respective families end up on opposite sides of the Civil War.